A BIBLIOMETRIC ANALYSIS OF MALAY VOWEL PHONOLOGY RESEARCH: MAPPING TRENDS FROM TRADITIONAL TO CONTEMPORARY SOURCES - Abidin, Afifah Zainal; Ahmad, Nor Aisyah; Zubir, Zuliana; Othman, Rabihah; Ibrahim, Nur Nabilah; Hashim, Anis Aleeya (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This bibliometric analysis examines the development and research patterns of Malay vowel phonology by systematically tracing its progression from traditional linguistic approaches to recent computational perspectives. Despite the expanding body of research in this field, a comprehensive mapping of its intellectual trends and major contributions remains lacking. The analysis was structured around a rigorous data search in the Scopus database, employing eight targeted keywords: Malay language, linguistic, accent, phonology, vowel, syllable, speech, and voiced sounds. Only English-language articles and conference papers published between 2010 and 2025 were included, resulting in a final dataset of 896 documents. The methodology incorporated a combination of Scopus Analyzer for extracting bibliometric indicators, OpenRefine for meticulous data cleaning and normalization, and VOSviewer for visualizing keyword co-occurrence, co-authorship networks, and international collaboration patterns. The results demonstrate a notable surge in publication output over the last five years, reflecting an increasing interest in both theoretical and applied aspects of Malay vowel research. Subject area analysis reveals a marked shift from traditional domains in arts and humanities towards more interdisciplinary integration with computer science, social sciences, and engineering. Thematic keyword analysis highlights core research clusters in speech perception, computational linguistics, and speech technology, with the United States, United Kingdom, and Germany leading in scholarly influence and collaborative strength. Meanwhile, the participation and visibility of Malaysia in global citation networks remain modest despite its direct contextual relevance. In conclusion, this study offers a data-driven perspective on the research landscape of Malay vowel phonology, identifying key thematic shifts, mapping collaborative networks, and providing valuable insights to inform future directions in both linguistic research and practical applications.